Self-Presentation of Multiple Account Users on Social Media (Dramaturgical Study of Instagram User Students in Pekanbaru) - Syimah Aqilah; Hesti Asriwandari (CV. Rayyan Dwi Bharata, 2024)
One of the social media that is famous in society is instagram. With the instagram application, users will easily get information, increase friendships, and even become a place to present themselves. Instagram makes it easy for its users to have more than one account through the multiple account feature. With this feature, users, who in this study are students, can have more than one account with different impressions on each account. The formulation of the problem in this research is the self-image construction carried out by students on each Instagram account and the reality of the lives of students who use instagram social media. The informants in the research were five students who were selected based on criteria, namely that they were active students at Pekanbaru universities, had more than one account on instagram social media, actively posted photos or videos on instagram accounts, had posts or a collection of highlights on the account that describes him has varied posts. The technique for determining informants is a purposive sampling technique. The method used is descriptive qualitative research. Researchers use Erving Goffman's Dramaturgical theory which explains interactions that occur in life like a drama performance. There is a front stage and a backstage. So, in this research this theory is applied to interactions carried out digitally on instagram social media. The results of this research are that the informant has many accounts on instagram with different impressions on each account. Different self-presentations are adjusted to the image you want to display. The informant admitted that he did the imaging to appear to present an ideal impression on his instagram account so that it was different from the reality of his life as a student.